The Widening Gap in Mortality by Educational Level in the Russian Federation, 1980–2001 - Murphy, Michael (© American Journal of Public Health 2006, 2006)
Objectives. We examined trends in the relation between educational level and adult mortality in the Russian Federation in the period 1989 through 2001. Methods. We used a convenience cohort based on survey respondents’ information about age, survival status, and educational level of close relatives, and applied modified indirect demographic techniques to stratify mortality rates by educational level in the study period. A random sample of 7172 respondents (response rate=61%) provided full information on 10440 relatives. Results. The mortality advantage of better-educated men and women in 1980 increased substantially by 2001. In 1980, life expectancy at age 20 for university-educated men was 3 years greater than for men with elementary education only, but was 11 years greater by 2001, reflecting not only declining life expectancy in less-educated men but also an improvement among better-educated men. Similar patterns were seen in women. Conclusions. The well-documented mortality increases seen in Russia after 1990 have predominantly affected less-educated men and women, whereas the mortality of persons with university education has improved, resulting in a sharp increase in educational-level mortality differentials.